2013
DOI: 10.1021/nn404427y
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Recognition Principles for Bionanocombinatorics: An Integrated Approach To Elucidate Enthalpic and Entropic Factors

Abstract: Bionanocombinatorics is an emerging field that aims to use combinations of positionally encoded biomolecules and nanostructures to create materials and devices with unique properties or functions. The full potential of this new paradigm could be accessed by exploiting specific noncovalent interactions between diverse palettes of biomolecules and inorganic nanostructures. Advancement of this paradigm requires peptide sequences with desired binding characteristics that can be rationally designed, based upon fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
371
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 139 publications
(395 citation statements)
references
References 82 publications
24
371
0
Order By: Relevance
“…The adsorption curve of each peptide at varying concentrations was fitted using a Langmuir isotherm, allowing values for kobs to be determined. 5 By utilising QCM-D data, the layer thickness of the peptide overlayer can be approximated 60 provided the effective density of the adhering layer is known. This density value was estimated by implementing the method reported by Fischer et al 61 Full details of these calculations are provided in "Overlayer Thickness Estimates from QCM-D data" in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The adsorption curve of each peptide at varying concentrations was fitted using a Langmuir isotherm, allowing values for kobs to be determined. 5 By utilising QCM-D data, the layer thickness of the peptide overlayer can be approximated 60 provided the effective density of the adhering layer is known. This density value was estimated by implementing the method reported by Fischer et al 61 Full details of these calculations are provided in "Overlayer Thickness Estimates from QCM-D data" in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…As described by Tang et. al, 5 the binding affinity of a particular sequence is characterized by the difference in Gibbs free energy between the bound and unbound states, ΔG =ΔH -TΔS, which is related to the equilibrium constant for binding, Keq = exp[ΔG/(RT)], where T denotes temperature. In previous studies, the high affinity of both peptides for TiO2 surfaces was suggested to be responsible for the formation of nanometer-sized crystalline nanoparticles of titania via a capping mechanism.…”
Section: Qcm Binding Analysismentioning
confidence: 99%
See 3 more Smart Citations